Had Youngest Toba Tuff (YTT, ca. 75 ka) eruption really destroyed living media explicitly in entire Southeast Asia or just a theoretical debate? An extensive review of its catastrophic event - Singh, Ajab; Srivastava, Ashok K. (Journal of Asian Earth Sciences: X, 2022)
•Humans were evolved in Africa.•No climate change occurred post YTT.•YTT impact was negligible. YTT eruption is viewed as a catastrophic event that resulted in deforestation, human bottlenecks and their migration across Southeast Asia and Africa. However, the question of whether the eruption had explicitly destroyed the vegetations, humans and animal populations in the Asia or, its impacts were localized and modest are still remain unanswered. To better comprehend the same, a systematic review of literature has thoroughly been carried out, specifically on the aspects of human inhabitation, vegetational scenario and animal remnants. The existing records suggest that humans were present in Africa long before the said eruption, however, their population had declined around 200 ka BP. It is also established that the humans began spreading out from the Africa in groups to other continents including India around 100 ka and witnessed dramatic growth between 60 and 80 ka. The vegetational scenario established on stable isotopes studies suggest existence of mixed C3-C4 vegetation in India around 100 ka which endured to sustain climatic fluctuations from Late Quaternary to Holocene period. The vertebrate remains indicate that the animal populations with genetic diversity existed in India between Late Pleistocene to Holocene. Existence of both diversified vegetation and animal remains plainly indicate that the living media was persistent and had experienced climatic changes long before and after the YTT eruption, concluding that the eruptive activity had insignificant impacts. Considering these summaries, the authors would like to point out that it would be a wrong attempt to correlate bottleneck of living populations with post-repercussions of YTT eruption as there is a long history of their endurance in various climatic conditions that occurred in the past and after the said eruption.